Effect Of Depo Medroxy Progesterone Acetat (DMPA) Injection Contraceptive Use On Blood Pressure In Regions Work Puskesmas Padang Door Tapanuli Selatan District Year 2022 - Rizki Noviyanti Harahap (Jurnal EduHealth, 2023)
Contraception is a device or drug used to prevent pregnancy. One type of injectable contraceptive that is widely used is Depo Medroxyprogesterone Acetate (DMP. The use of Depo Medroxyprogesterone Acetate (DMPA) must be considered because in addition to having a positive effect, it also has a negative effect, one of which affects blood pressure. This study aims to determine the effect of the duration of contraceptive use. Injection of Depo Medroxy Progesterone Acetate (DMPA) Against Blood Pressure in the Working Area of Pintu Padang Health Center, South Tapanuli Regency in 2022. This study uses parametric statistical analysis with an observational approach. The population in this study were all mothers who used depo medroxyprogesterone acetate contraception in the working area of the Pintu Padang Health Center as many as 257 mothers. The sampling technique using the Accidental Smpling technique was 26 people. The results showed that the duration of the use of Depo Medroxy Progesterone Acetate (DMPA) injectable contraceptives in the working area of the Pintu Padang Health Center was mostly 2-4 years, the maternal blood pressure in the Pintu Padang health center was mostly 120-139/80-89 mmHg. The results of the Paired Sample-Test test obtained a p-value of 0.031 < =0.05, then H0 is rejected, meaning that there is an effect of the duration of the use of Depo Medroxy Progesterone Acetate (DMPA) injectable contraception on blood pressure in the working area of the Pintu Padang Health Center, South Tapanuli Regency in 2022.The suggestion in this study is that the work of the Pintu Padang Health Center in South Tapanuli Regency can inform mothers about the side effects of injectable contraceptives 3 months before being injected to the mother.